1988
DOI: 10.1073/pnas.85.13.4686
|View full text |Cite
|
Sign up to set email alerts
|

Active human immunodeficiency virus protease is required for viral infectivity.

Abstract: Retroviral proteins are synthesized as polyprotein precursors that undergo proteolytic cleavages to yield the mature viral proteins. The role of the human immunodeficiency virus (HIV) protease in the viral replication cycle was examined by use of a site-directed mutation in the protease gene. The HIV protease gene product was expressed in Escherichia coHl and observed to cleave HIV gag p55 to gag p24 and gag p17 in vitro. Substitution of aspartic acid residue 25 (Asp-25) of this protein with an asparagine resi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
861
1
13

Year Published

1992
1992
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,277 publications
(886 citation statements)
references
References 24 publications
6
861
1
13
Order By: Relevance
“…Structural proteins and enzymes that are essential to the life cycle of the HIV virus are products of the enzymatic cleavage of the polyprotein products of the gag and pol viral genes (Kohl et al, 1988;Seelmeier et al, 1988). The enzyme responsible for the cleavage reactions is the HIV aspartyl protease, and inhibition of this protease leads to the production of noninfectious viral particles.…”
mentioning
confidence: 99%
“…Structural proteins and enzymes that are essential to the life cycle of the HIV virus are products of the enzymatic cleavage of the polyprotein products of the gag and pol viral genes (Kohl et al, 1988;Seelmeier et al, 1988). The enzyme responsible for the cleavage reactions is the HIV aspartyl protease, and inhibition of this protease leads to the production of noninfectious viral particles.…”
mentioning
confidence: 99%
“…Dimerization and activation of the retroviral PRs is presumably concentration dependent and therefore likely to occur once viral capsid assembly has begun increasing the colocalization of viral proteins. Inhibition of this dimerization step would prevent the activation of the viral PR and, in turn, prevent the polyprotein processing, which is essential for viral maturation and infectivity (Kohl et al, 1988). The ability of oligopeptides to interfere with formation of a protein complex has been previously documented in vitro for two herpes simplex virus systems, the enzyme ribonucleotide reductase (Dutia et al, 1986;McClements et al, 1988), and the regulatory protein VP16 (Haigh et al, 1990).…”
mentioning
confidence: 99%
“…Excision of individual enzymes and structural proteins is felt to be performed by the aspartyl protease, HIV-1 PR, and largely occurs in budding virions. 21 Unexpectedly, Western blot analyses showed that SV(AT) inhibited processing of p55 Gag in SupT1 cells and in primary human lymphocytes; high levels of uncleaved p55 Gag protein accumulated within cells and were detected in virus particle progeny recovered from these cells after transduction with SV(AT).…”
Section: Inhibition Of Hiv-1 Replication By a 1 Atmentioning
confidence: 98%
“…21 Just as cellular serine protease activity is fundamentally important to envelope, viral aspartyl protease activity is required for gag proprotein processing: both processes are necessary to generate infectious viral progeny. 19,22 Thus, gene delivery to inhibit proteolytic cleavage of envelope and gag precursors could represent a new approach for gene therapy to interfere with HIV-1 infectivity.…”
Section: Introductionmentioning
confidence: 99%